Design and Application of Control System for All-vanadium Redox Flow Energy Storage - YANG Linlin; SHEN Hua; LIN Youbin (Kongzhi Yu Xinxi Jishu)
The all-vanadium redox flow technology has garnered significant attention in the energy storage field, due to its attributes of high safety, high reliability, environmental friendliness, and power-capacity decoupling. Within all-vanadium redox flow energy storage setups, the control system is deemed the core, evolving towards enhanced integration, precision, and intelligence. This paper seeks to elevate these benchmarks and advance technological levels in the localization of this system. Based on a review of technologies related to the entire control system, this study conducted an in-depth analysis concerning key parameters and control logic. Addressing some key concerns within the control system, solutions were proposed, including temperature control, operational modes, and state-of-charge (SOC) estimation. The subsequent study focused on designing architecture for monitoring and managing all-vanadium redox flow energy storage systems through a modular approach, aiming at a more adaptable, elastic, and scalable control system. Furthermore, the developed control system was verified through practical implementation in commercial energy storage and applications under grid-connected environments. Based on the study outcomes, this paper also explores potential future technological trends for all-vanadium redox flow energy storage control systems in various aspects such as operation, maintenance, losses, and equilibrium.